Tablets at the bedside - iPad-based visual field test used in the diagnosis of Intrasellar Haemangiopericytoma: a case report - Nisha Nesaratnam; Peter B. M. Thomas; Ramez Kirollos; Algis J. Vingrys; George Y. X. Kong; Keith R. Martin (BMC Ophthalmology, 2017)
Abstract Background In the assessment of a pituitary mass, objective visual field testing represents a valuable means of evaluating mass effect, and thus in deciding whether surgical management is warranted. Case presentation In this vignette, we describe a 73 year-old lady who presented with a three-week history of frontal headache, and ‘blurriness’ in the left side of her vision, due to a WHO grade III anaplastic haemangiopericytoma compressing the optic chiasm. We report how timely investigations, including an iPad-based visual field test (Melbourne Rapid Field, (MRF)) conducted at the bedside aided swift and appropriate management of the patient. Conclusions We envisage such a test having a role in assessing bed-bound patients in hospital where access to formal visual field testing is difficult, or indeed in rapid testing of visual fields at the bedside to screen for post-operative complications, such as haematoma.